Authentic Leadership Fostering Creativity in Start-ups: Mediating Role of Work Engagement and Employee Task Proactivity. Issue 2 (May 2021) - Sengupta, Santoshi; Sharma, Swati; Singh, Aishwarya
This study investigates the effect of authentic leadership (AL) on employee creativity and the mediating role of work engagement (WE) and employee task proactivity (ETP) in the context of start-ups. Data collected from 300 leaders and 300 employees of Indian start-ups were analysed using structural equation modelling. The findings suggest that AL has direct and significant effects on creativity and the same is mediated by WE and ETP. For a start-up, it is essential that employees perceive their founders or leaders to have high moral perspective, clear sense of self-awareness and exhibit transparency in their behaviours with their followers. Such behaviours motivate the followers to invest soulfully in their work and do things in a proactive manner, which then leads to creativity. For any start-up to succeed, both a strong form of positive leadership and high levels of creativity from employees are required.